Formulation and evaluation of carnosic acid nanoparticulate system for upregulation of neurotrophins in the brain upon intranasal administration. (January 2013) - Vaka, Siva Ram Kiran; Shivakumar, H.N.; Repka, Michael A.; Murthy, S. Narasimha
<x xml:space="preserve">Abstract</x> To develop formulations of carnosic acid nanoparticles and to assess their in vivo efficacy to enhance the expression of neurotrophins in rat model. Carnosic acid loaded chitosan nanoparticles were prepared by ionotropic gelation technique using central composite design. Response surface methodology was used to assess the effect of three factors namely chitosan concentration (0.1–1% w/v), tri-poly phosphate concentration (0.1–1% w/v) and sonication time (2–10 min) on the response variables such as particle size, zeta potential, drug encapsulation efficiency and drug release. The neurotrophins level in the rat brain upon intranasal administration of optimized batch of carnosic acid nanoparticles was determined. The experimental values for the formulation were in good agreement with those predicted by the mathematical models. A single intranasal administration of the optimized formulation of carnosic acid nanoparticles was sufficient to result in comparable levels of endogenous neurotrophins level in the brain that was almost on par with four, once a day intranasal administration of solution in rats. The results clearly demonstrated the fact that nanoparticulate drug delivery system for intranasal administration of carnosic acid would require less number of administrations to elicit the required pharmacological activity owing to its ability to localize on the olfactory mucosal region and provide controlled delivery of carnosic acid for prolonged time periods.